Benefits of Gamified Learning in Physical Education Students: A Systematic Review - Ferriz-Valero, Alberto; Agulló-Pomares, Genís; Tortosa-Martínez, Juan (Apunts. educació física i esports, 2023)
The aim of the present study was to examine the relationship between depressive symptomatology and persistence in physical exercise in the presence of physical harm or injury. Data obtained from 345 university students (52.50% female) aged 18-37 years (Mage = 21.67; SDage = 3.48) who reported engaging in recreational exercise at least once a week were analysed. The data were analysed using regression analyses using a robust maximum likelihood (RML) estimation method. These analyses accounted for the effects of age, gender, body mass index, perceived health status, frequency of physical exercise, and level of risk of eating disorders. In the first regression analysis, depressive symptomatology (β = .193, 95% CI = .098 to .288, p < .001) explained a significant proportion of variance in exercising in the presence of physical harm or injury (18.30%). In the second regression analysis, exercising in the presence of physical harm or injury (β = .186, 95% CI = .111 to .261, p < .001) explained a significant proportion of variance in depressive symptomatology (18.80%). The present findings suggest the need to further examine the variables that could condition the relationship between depressive symptomatology and exercising in the presence of physical harm or injury, as well as the possible causal nature of this relationship.